Empowering local communities to make lifestyle changes: is the Health Mela a potential solution?. Issue 2 (21st July 2020) - Watson, Joseph; Satyan, Rajbhandari; Gupta, Romesh; Myers, Martin; Campbell, Robert; Macphie, Elizabeth
Abstract : Background: Health Melas are community-led public health events held in the North West of England that provide health information and free health checks. This descriptive observational study evaluates whether Health Melas are able to identify undiagnosed cardiovascular disease (CVD) risk factors in hard-to-reach communities and encourage individuals to make lifestyle changes. Methods: Attendees ≥18 years at three separate Health Melas in 2016–2017 were invited to participate in screening and counselling for CVD risk factors as part of a Health MOT. Information was collected about demographics, CVD risk factors, blood pressure, total cholesterol, blood sugar and attendees' feedback. QRISK2 scoring system was used to estimate CVD risk. Results: 375 attendees completed a questionnaire. The highest proportion (36.9%) of attendees were from areas of the lowest Index of Health Deprivation and Disability quintile; 38.8% were of South Asian ethnicity. Of the attendees who were eligible for a free National Health Service Health Check, 9.1% had received one. Overall, 57.5% of all attendees had a QRISK2 score ≥10% (of whom 56.9% were not on statins), 92.2% of attendees believed the Health Mela will help them to make lifestyle changes, 98.2% said they had improved their understanding of their health, and 99.6% thought the Health Mela was useful. 73.6% of those who had received a previous Health MOT reported making lifestyle changes. There was a positive correlation between South Asian ethnicity and QRISK2 score. Conclusion: This study suggests the Health Melas successfully involve South Asian populations and people from a lower Index of Health Deprivation and Disability. Attendees felt the events were useful, improved understanding of their health needs and encouraged them to make lifestyle changes. High rates of modifiable CVD risk factors were newly identified and a high proportion of attendees were found to be at intermediate to high risk of CVD.